(untitled) (Journal of the College of Basic Education, 2025)
Margaret Mitchell’s Gone with the Wind (1936) is the only full-length narrative she ever wrote; however, she also wrote other forms of fiction. The novel was written in the 1930s, which was a time of tremendous economic difficulties and hardships. In fact, the Great Depression occurred in 1929, during the writing of the novel, and was by far the worst economic recession the United States of America has ever experienced. In terms of settings, the novel depicts the American Civil War, describes the radical changes created by it and portrays the sufferings of the Southern people in attempting to survive it. Therefore, the novel is broadly perceived to be dealing with and presenting survival as its principal concept. In that order, there have been numerous studies that have investigated the topic of survival in the novel. Other research papers have explored various themes in the novel, including feminism, historical and cultural relevance, the portrayal of women, and slavery. Yet, investigating the ways and strategies of adaptation for survival in the novel in a single and comprehensive effort seems either an untouched topic or been referred to slightly and as a secondary problem of study. In view of that, the current research paper aims to examine the adaptation for survival in Margaret Mitchell’s novel Gone with the Wind. The study also intends to address the different strategies, ways and means of adaptation for survival as shown in the novel and enacted by its characters. The study at hand is theoretical and relies on a critical analytic approach in its discussion and analysis. In terms of findings, the study reveals that accepting change, acclimatizing to new changes, working, flexibility, breaking with traditions and ignoring people’s expectations have represented the major techniques of adaptation for survival in the novel.